Organizational Culture Shapes Performance in University Handball Teams: Budaya Organisasi Membentuk Performa Tim Bola Tangan Universitas - Omar noori Abbas (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: The management of university sports teams is a complex field requiring coordination between university administrations, coaches, and players. University championships serve not only as competitive events but also as educational platforms that enhance students’ personal and social development. Specific Background: Organizational culture plays a fundamental role in the success of university sports teams by shaping relationships, influencing performance, and fostering collaboration. Despite its importance, limited research has examined the impact of organizational culture on sports team management, particularly in university handball teams. Knowledge Gap: Existing studies have not fully explored the interplay between organizational culture dimensions—such as leadership, teamwork, responsibility, and transparency—in enhancing sports performance and team interaction. Aims: This study aims to analyze the organizational culture in university handball team management, determine its influence on performance, and identify key challenges. Results: Findings indicate that high-level university teams exhibit a strong organizational culture. Cooperation and teamwork have the most significant impact, followed by leadership, responsibility, and transparency. Novelty: This study provides empirical evidence on how specific cultural dimensions influence university sports management, emphasizing teamwork’s dominant role. Implications: The results offer insights for sports administrators and policymakers to strengthen organizational culture, ultimately improving team performance and fostering a more cohesive sports environment. Highlights: Teamwork Matters – Strongest influence on organizational culture in sports teams. Leadership Guides – Enhances performance and shapes team culture. Transparency Counts – Justice and responsibility improve team dynamics. Keywords: Organizational culture, university sports management, teamwork, leadership, handball teams